The future of democracy: the end of democracy as we know it. Issue 10 (21st June 2019) - Goede, Miguel
Abstract : Purpose: The purpose of this article is to explore the future of democracy, given the transition the countries of the world are experiencing. Methodology: The paper draws on literature concerning democracy, ICT and artificial intelligence. A framework for understanding the working of democracy is developed. This framework or model is tested in 20 countries, and conclusions are presented. Findings: Globally, there is a shift taking place away from representative democracy toward less democratic forms of government. Originality: Most studies are implicitly dogmatic in assuming that representative democracy is a superior form of government. The influences of corporations, media and the elite are moving representative democracy away from the ideal of democracy. Conclusions: The future of democracy is uncertain. It is not likely that representative democracy will become the universal form of government. Global government is possible, but it is not likely to be a representative democracy.